Round window sealing with steroid-soaked sponge in sudden sensorineural hearing loss - Putranto, Fikri Mirza; Safitri, Eka Dian; Shafira, Ardys (PERHATI-KL, 2024)
Background: A rescue treatment is needed in cases of Sudden Sensorineural Hearing Loss (SSNHL)which fail to obtain complete hearing restoration after conservative steroid therapy. In order to acquirebetter access of steroid to the cochlea, sealing the round window with a sponge soaked in steroid couldbe considered as an alternative delivery strategy. Purpose: To review the evidence about the impact ofround window sealing in SSNHL patients whose hearing failed to recover completely after treated withsystemic and/or intratympanic steroid. Cases: Seven patients with SSNHL, who had experienced either noor slight response to previous systemic and/or intratympanic steroid administration, underwent transcanalround window sealing with steroid-soaked sponge. Pure Tone Audiometry (PTA) results and symptoms(hearing loss, tinnitus, vertigo) were compared pre- and post-operatively. Five patients reported betterhearing and tinnitus symptom. Method: A scoping review was made by conducting literature searchingat Cochrane, Pubmed, and Google Scholar using keywords “sudden sensorineural hearing loss”, AND“round window sealing”, and their relevant synonymous terms, employing Boolean operators. Result: Atotal of 8 observational studies with 430 subjects met the inclusion criteria. Time measurement of hearingimprovement range from 6 days until 1 year. Most of the studies agreed that the procedure of sealingthe round window had a positive impact on hearing improvement. Conclusion: This study revealed thatround window sealing with steroid-soaked sponged could be considered as an alternative approach forpatients with SSNHL who failed in conservative therapy. Keywords: “round window sealing; sudden sensorineural hearing loss; transtympanic steroid”